The sonic camera: Intermodality and intermediality in contemporary jazz composition - Cosper, David (Jazz Research Journal, 2015)
In this work, I explore the resonance and recurrence of visual metaphors in the discourse surrounding contemporary jazz composition and performance, much of which I suggest resists analytical approaches privileging cyclicity in form and relationships between pre-composed and improvised tonal language. I argue that, as a recurrent conceptual glitch, these analytical approaches often focus exclusively on performative process rather than on listener experience and on strictly aural rather than synesthetic models of listener subjectivity. As an alternative, I propose a cinematographic narrative approach based on theories of visual subjectivity and the composition of visual images. As an example, I discuss the music of bassist and composer Ben Allison.